One-Step Synthesis of Carbon Nitride Nanosheets for Photoremediation of Toxic Organic Dyes Waste in Aquatic Environment - Huwaida Ikbar; Muhammad Hakim Muzakky; Harry Pramudya Rivelino; Anatta Wahyu Budiman (CHEMICA: Jurnal Teknik Kimia, 2020)
Graphitic Carbon nitride (g-C3N4) has been taking the attention of scientists because of its potential applications as a catalyst for organic synthesis, electrodes, photocatalyst, and hydrogen storage material. The g-C3N4 has also excellent chemical stability, special optical characteristics, and high thermal stability. Moreover, it only consists of carbon and nitrogen elements that make it safer for the environment than metal-based catalysts. Various techniques have been introduced to improve g-C3N4 photocatalytic efficiency as a combination with other semiconductors and the modification of morphology like porous g-C3N4 or nanostructures g-C3N4. When compared with g-C3N4 bulk, g-C3N4 Nanosheets have many advantages including high efficiency, low cost, environmentally friendly, and easy to produce on a large scale. This review contains an overview of the one-step synthesis method from melamine and ammonium chloride for g-C3N4 nanosheets as well as characteristics and potential applications in dyes photoremediation.